Etika Komunikasi di Media Sosial pada Remaja Masjid Himpunan Muda-Mudi Al-Ikhlas Kelurahan Dwikora Kecamatan Medan Helvetia - Ayu Zulia; Cici Anggraini; Dinda Arwilda Sembiring; Isra Della Aulia; Rizky Pratama (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
The massive development of technology today has penetrated into the increasing number of social media. Instagram, Facebook, Tik Tok, Twitter, and so on which are currently consumed by teenagers in Indonesia. Of course there are many benefits to be gained from social media, such as a place for healthy dialogue, creating prosperity, and providing a positive influence. However, it is undeniable that at least social media also has negative impacts, such as the spread of hoax news, hate speech, and the spread of negative doctrines. Therefore, the Real Work Lecture (KKN) team from the State University of North Sumatra (UINSU) tried to observe social media activities, especially for mosque youths in Dwikora Village, Medan Helvetia District. The purpose of this study was to find out about social media activities and their responses that tend to have a negative impact. This study uses a descriptive method with qualitative data analysis which only describes the phenomena that occur in the surrounding environment. The technique used in this research is purposive sampling by selecting some of the required informants, especially the youth of the Al-Ikhlas mosque, Dwikora Village, Medan Helvetia District.